2020
DOI: 10.3389/fcell.2020.00297
|View full text |Cite
|
Sign up to set email alerts
|

SP1/AKT/FOXO3 Signaling Is Involved in miR-362-3p-Mediated Inhibition of Cell-Cycle Pathway and EMT Progression in Renal Cell Carcinoma

Abstract: Emerging evidence has indicated that dysregulation of miR-362-3p is involved in the initiation and progression of several types of human cancers. However, the molecular mechanism of miR-362-3p in renal cell carcinoma (RCC) is still not completely clear. In this study, we found that miR-362-3p was frequently down-regulated in human RCC tissues. Overexpression of miR-362-3p in RCC cells significantly suppressed the proliferation, cell cycle and motility in vitro and in vivo via regulating AKT/FOXO3 signaling. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…miR-572 likewise represents an oncomir in RCC pathogenesis by enhancing proliferation and invasion and inhibiting tumor cell apoptosis by suppressing NF2/Hippo signaling (Guan et al, 2018;Pan et al, 2018a). On the other hand, miR-28-5p (Wang et al, 2016) and miR-362 (Zou et al, 2016;Zhu et al, 2020) were suggested as tumor-suppressive miRNAs in RCC, although the miR-362 serum levels were increased in the study by Wang et al (2015).…”
Section: Cssmentioning
confidence: 98%
“…miR-572 likewise represents an oncomir in RCC pathogenesis by enhancing proliferation and invasion and inhibiting tumor cell apoptosis by suppressing NF2/Hippo signaling (Guan et al, 2018;Pan et al, 2018a). On the other hand, miR-28-5p (Wang et al, 2016) and miR-362 (Zou et al, 2016;Zhu et al, 2020) were suggested as tumor-suppressive miRNAs in RCC, although the miR-362 serum levels were increased in the study by Wang et al (2015).…”
Section: Cssmentioning
confidence: 98%
“…The role of SP1 in RCC had also been investigated before. SP1 could bind to the promoter region of SNHG14 to upregulate its expression to promote migration and invasion of ccRCC (33,34). Previous study also demonstrated that dephosphorylated Sp1 was more tightly associated with chromatin than its phosphorylated counterparts from either resting or mitotic cells (30), which suggested that the status of phosphorylation would affect the chromatin accessibility.…”
Section: Discussionmentioning
confidence: 95%
“…The treatment of renal malignancies therefore represents an ongoing challenge. Various studies have reported possible mechanisms and causes of kidney carcinomas [4][5][6][7][8][9][10][11] ; however, the precise mechanism of RCC remains unclear.…”
Section: Introductionmentioning
confidence: 99%